Microwave Promoted Regeneration of Carbonyl Compounds from Oximes Using N, N-Dichloro Poly(Styrene-co-divinylbenzene)Sulphonamide Resin - A.G. Beldar; Mamta Sharma (E-Journal of Chemistry)
An efficient, economically viable and operationally simple method was developed for deoximation of oximes (of ketones and aldehydes) to their corresponding carbonyl compounds using polymer beads of N, N-dichloro poly(styrene-co-divinylbenzene)sulphonamide resin. Polymeric reagent offered speedy conversion and substantial yields of products under mild condition and is recyclable. Deoximation was monitored by the use of 13C NMR.